Awareness and Practice of Blood Donation Among Medical Students of AIMC/FJMU - KHURRAM SHAHZAD, BILAL HASSAN, MUHAMMAD IMRAN, SHABAHAT ALI (Journal of Fatima Jinnah Medical University, 2018)
Background: The level of awareness and practice concerning blood donation among the medical students is important to be understood as they are projected to convey the information to the general population about the need of voluntary blood donation. Aims and Objective: The evaluation of knowledge level and practice about blood donation amongst medical students of Allama Iqbal Medical College and Fatima Jinnah Medical University, Lahore. Study Design: Cross sectional study. Study Setting: Study was performed among the students of AllamaIqbal Medical College, affiliated with Jinnah Hospital, Lahore. and Fatima Jinnah Medical University, affiliated with Sir Ganga Ram Hospital Lahore. Duration of Study: 3 September to 8 December, 2016. Sample Size: 550 Medical Students. Sampling Technique: Sampling Technique used was non probability convenient technique. Results: There were550 respondents,162 males and 388 females. Among 162males 94(58%) were donor and68(41.9%) didn’t donate blood. Among 388 females 44 (11.3%) were donor and 344(88.7%) didn’t donate blood. Causes: for not donating the blood were, weakness (23.8%),fear of needle prick (5.6%) , fear of blood borne diseases (5.3%), fright of becoming fat (3.3%) and no proper reason (37.5%).There was no note worthy dissimilarity in awareness amongst males and females, but blood donation practices were found to be markedly higher in males. Conclusion: Blood donation compaigns and seminars are not enough to motivate them to donate blood, Collaborative awareness sessions may be arranged to strength then practice of blood donation.